Analisis Potensi Diri Manusia Dengan Menggunakan Pendekatan Psikologi Humanistik - Aldi Gilang (DAWUH : Islamic Communication Journal, 2024)
This research aims to explain self-potential using a humanistic psychology approach. According to Halid, self-potential must be developed and must be known because humans will develop in the world of education and career if they have self-potential. The research method uses literature studies by analyzing 20 journals as primary data. Data analysis with the first stage determining the theme, the second stage selecting journal articles that are relevant to the theme and in accordance with the deadline (last 5 years), the third stage the journal article review process, the fourth stage categorization and the fifth stage drawing conclusions. The research results show that self-potential is related to various aspects of human life, including social aspects (relationships, family, work, education). Humanistic psychology also has a positive impact on education, where humanistic education strives to develop individuals in all aspects. This development is emotional, social, mental and also the interests of human talents themselves. This flow was characterized by Abraham Maslow and Carl Rogers, humanistic psychology emerged in the 1940s as a reaction to dissatisfaction with psychoanalytic and behavioristic approaches. Using a humanistic psychological approach is very relevant for humans to find out the potential hidden within